Desempenho de cabritos alimentados com variedades de palma forrageira resistente a cochonilha do carmim. - Sousa, Francinilda Alves de (2015)
This study aimed to evaluate diets with different varieties of cactus forage resistant cochineal carmine performance of young goats without defined breed. The experiment was conducted at the Experimental Station of UFPB, located in São João do Cariri-PB. 40 young goats were used without defined breed, with average initial weight of 15 ± 0.96 kg and approximately five months of age in a randomized block design, 4 X 10, four diets and ten repetitions, duration the experiment were 80 days in which 15 were for adaptation diets. The treatments consisted of four diets: control (Tifton grass hay, corn bran and soy bean meal), and diets increased with the varieties of cactus forage (elephant ear, Baiana and miuda).The animals feeding was carried out 2 times a day for 7 h to 15 h. Each animal leftover samples were collected daily and the material offered every 15 days for subsequent determination of nutrient content. For the determination of total weight gain and daily, the young goats were weighed weekly and, for feed, was considered the dry matter intake in kg / day divided by average daily gain weight. To determine the digestibility of dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF) and total carbohydrates (TC), collections were made from animal feces in an in vivo digestibility trial for 5 dias. As observations concerning the feeding behavior of the animals were made into three distinct periods, over 24 uninterrupted hours. The observed and recorded behavioral variables were: idleness, eating, ruminating. The harvest of rumen fluid was performed every 30 days after the day of the beginning of the trial, four hours after the first food supply. After collecting pH readings were taken, and further analysis of AGV. and N-NH3.A collecting blood from all animals was taken to zero and four hours for subsequent biochemical analysis. Slaughter of achievement occurred when the block reached 22 kg of average body weight for carcass quantitative analysis. There were significant differences (P <0.05) for the CMS variables (g / day), CMS (% PC), nitrogen balance and weight gain. Having significance for CMS (P0,75), rumination time, rumination efficiency, pHruminal and NH3 (P <0.05). The N-NH 3 from the control diet showed higher concentrations compared diets with varieties of Baiana and palm miuda. Evaluated blood parameters did not differ between treatments. The use of diets with different varieties of cactus forage SPRD goats do not cause metabolic disorders such does not influence weight gain